Platelet Rich Plasma and Knee Surgery. (2nd September 2014) - Sánchez, Mikel; Delgado, Diego; Sánchez, Pello; Fiz, Nicolás; Azofra, Juan; Orive, Gorka; Anitua, Eduardo; Padilla, Sabino
Abstract : In orthopaedic surgery and sports medicine, the knee joint has traditionally been considered the workhorse. The reconstruction of every damaged element in this joint is crucial in achieving the surgeon's goal to restore the knee function and prevent degeneration towards osteoarthritis. In the last fifteen years, the field of regenerative medicine is witnessing a boost of autologous blood-derived platelet rich plasma products (PRPs) application to effectively mimic and accelerate the tissue healing process. The scientific rationale behind PRPs is the delivery of growth factors, cytokines, and adhesive proteins present in platelets and plasma, as well as other biologically active proteins conveyed by the plasma such as fibrinogen, prothrombin, and fibronectin; with this biological engineering approach, new perspectives in knee surgery were opened. This work describes the use of PRP to construct and repair every single anatomical structure involved in knee surgery, detailing the process conducted in ligament, meniscal, and chondral surgery.